TITLE: CONSTRUCTION OF AUTOMATIC LINES CONNECTING SEVERAL MECHANICAL OPERATIONS IN PROCESSING LEATHER SEMI-FINISHED PRODUCT - B G.A. , Bakhadirov (International Journal of Psychosocial Rehabilitation, 2020)
This paper studies the construction of automatic lines that connect several operations involved in processing leather semi-finished product. These automatic lines are deemed to provide improved product quality and production efficiency. As well as this, the kinematics of the cutter shaft is another focused area of this research. The paper proposes a conveyor that ensures a stable operation of automatic lines of leather semi-finished product processing, and tests whether the conveyor is effective indeed. The results suggest that, without stopping the technological cycle of the sheet material processing, it ensures stable functioning of the automatic line. In obtaining the findings, mathematical modelling is selected as the key method, and MS Excel spreadsheet is used to derive the results.